2022
DOI: 10.1101/2022.07.12.499387
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Effects of N-linked Glycosylation on SLC6 Transporters

Abstract: Membrane transporters of the solute carrier 6 (SLC6) family mediate various physiological processes by facilitating the translocation of amino acids, neurotransmitters, and other metabolites. In the human body, these transporters are tightly controlled through various post-translational modifications with implications on protein expression, stability, membrane trafficking, and dynamics. While N-linked glycosylation is a universal regulatory mechanism among eukaryotes, the exact molecular mechanism of how glyco… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…Increasing evidences have shown that post-translational modifications such as glycosylation is implicated in transporter stability and membrane trafficking [29][30][31]. Therefore, we investigated whether PIGT influences the glycosylation of GLUT1.…”
Section: Post-translational Modification Of Glut1 By Pigtmentioning
confidence: 99%
“…Increasing evidences have shown that post-translational modifications such as glycosylation is implicated in transporter stability and membrane trafficking [29][30][31]. Therefore, we investigated whether PIGT influences the glycosylation of GLUT1.…”
Section: Post-translational Modification Of Glut1 By Pigtmentioning
confidence: 99%
“…Although cholesterol is physiologically present in the human membrane environment, it has been shown to bias the conformations of membrane peoteins 82,83 . As such, the cholesterol molecules were excluded to prevent unintended inhibition of transporter dynamics 84 . The CHARMM36m force field was used to describe the proteins 85 , and the parameters for substrate TCA were generated using the CHARMM general force field (CGenFF) 86 .…”
Section: Simulation Systems Setup and Equilibrationmentioning
confidence: 99%
“…This point was emphasized by the Shukla group in their 2022 study on the effects of N-linked glycosylation on SLC6 transporters. 226 From over 1 ms of independent simulations using combinatoric glycosylation patterns across four different SLC6 transporters, Chan and Shukla concluded that the impacts of glycosylation should be characterized at a per-protein level regardless of shared function within a family. 226 And amazingly, across all studies implementing the ''single'' or ''few'' trajectories approach, decent extents of conformational change, and the conversion between different states, could be observed in very short amounts of simulation time.…”
Section: Summary Of Ptm Simulations Using ''Single'' or ''Few'' Traje...mentioning
confidence: 99%